The use of feedback in written reports and portfolio: an assessment for learning strategy - Santos, Leonor (2010)
This paper pretends to study the potentialities of feedback, particularly in the development of a written report in two phases and in portfolio; and the main difficulties that teachers has to face concerning this assessment practice. Through a meta-analysis concerning different studies, it is possible to say that oral or written feedback, intentionally provided to students of several ages, may enable them to develop their self-assessment capacity and to get close of the expected product. However, the type of student and his or her perceptions may influence the effectiveness of feedback. Even for experience teachers, this practice maintains complex.